Exploring barriers, motivators and solutions to achieve a healthy lifestyle among undergraduate student nurses. (24th February 2022) - Austin, Daniela; May, Jon; Andrade, Jackie; Nichols, Andy
Abstract : Background: Many preregistration student nurses tend to be overweight or obese and have unhealthy lifestyles. Aims: This study aimed to quantify the prevalence of these issues, to identify barriers to adopting a healthy lifestyle as well as potential solutions, and to explore the use of smartphone health apps. Methods: An online questionnaire examined diet and physical activity habits, general health and attitudes to eHealth. An in-class questionnaire with a new sample assessed current lifestyle, barriers to healthier living, support needed to achieve goals and the use of health apps. Findings: Half of student nurses were overweight or obese and only 41% met the recommended levels of physical activity. An in-class questionnaire revealed that more than half of them wanted to have a better diet and to exercise more. Conclusion: Generally, student nurses were not satisfied with their current lifestyles. A lack of motivation and time were the most frequently reported barriers; an intervention focusing on motivational support could be an acceptable and effective means of achieving and sustaining positive behaviour change.